Novel Molecular Imaging Approach for Subclinical Detection of Iritis and Evaluation of Therapeutic Success - Xie, Fang (American Society for Investigative Pathology, 2010)
There is an urgent need for early diagnosis in medicine, whereupon effective treatments could prevent irreversible tissue damage. Acute anterior chamber inflammation is the most common form of uveitis and a major cause of vision loss. The proximity of the iris vasculature to the light-permeable cornea and its involvement in ocular inflammation make it an ideal target for noninvasive molecular imaging. To accomplish this, carboxylated fluorescent microspheres (MSs) were conjugated with recombinant P-selectin glycoprotein ligand-1 and systemically injected in endotoxin-induced uveitic animals. MS adhesion in the microcirculation of the anterior and posterior chamber was visualized by intravital microscopy and scanning laser ophthalmoscopy. In iritic animals, significantly higher numbers of recombinant P-selectin glycoprotein ligand-1-conjugated MSs adhered to the endothelium (P = 0.03) matching the increase in leukocyte adhesion. Conjugated MSs specifically interacted with firmly adhering leukocytes, allowing quantification of the endogenous immune response. Topical eye drop treatment with dexamethasone (P < 0.01) or cyclosporine A (P < 0.01) significantly lowered MS adhesion in iris vessels. Surprisingly, topical dexamethasone significantly reduced MS interaction in the fundus vessels (P < 0.01), while cyclosporine A did not. In vivo MS accumulation preceded clinical signs of anterior uveitis and leukocyte adhesion in iris vasculature. This work introduces noninvasive subclinical detection of endothelial injury in the iris vasculature, providing a unique opportunity for quantifying vascular injury and immune response in vivo.